Exploring Reluctance in Halal Food Awareness among Millennials: A Modified TPB Approach - Razak, Syaparuddin (Universitas Muhammadiyah Yogyakarta, 2024)
Integrating the Theory of Planned Behavior (TPB), this study adapts and augments the model with the concept of lacking halal awareness, establishing a robust theoretical framework. The investigation explores the impact of factors like lack of halal awareness, negative attitude, low subjective norms, and perceived low behavioral control on the formation of weak intentions. Furthermore, the study delves into the mediating role of weak intention, investigating its influence on the relationship between the proposed adoption factors and the reluctance among millennials to purchase halal food products. The analysis involves 203 responses gathered through an online survey. The results reveal nuanced insights. While the lack of halal awareness exerts no significant effect on weak intention, negative attitude, low subjective norms, and perceived low behavioral control significantly impact its formation. Interestingly, weak intention is not observed as a mediator between the lack of halal awareness and the reluctance to purchase halal food products among millennials. However, it fully mediates the link between negative attitude, low subjective norms, perceived low behavioral control, and the reluctance to purchase such products. These findings hold implications for consumers, producers of halal food products, and the Indonesian Government. By unraveling the complexities of halal food awareness reluctance, the study contributes to valuable insights for informed decision-making, strategic planning, and effective engagement within the halal market.